2019
DOI: 10.4047/jap.2019.11.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatments on the bond strength of indirect resin composite to resin matrix ceramics

Abstract: PURPOSE The purpose of this study was to evaluate the shear bond strength (SBS) of an indirect resin composite (IRC) to the various resin matrix ceramic (RMC) blocks using different surface treatments. MATERIALS AND METHODS Ninety-nine cubic RMC specimens consisting of a resin nanoceramic (RNC), a polymer-infiltrated hybrid ceramic (PIHC), and a flexible hybrid ceramic (FHC) were divided randomly into three surface treatment subgroups (n = 11). In the experimental group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
10
1
1
Order By: Relevance
“…The results of this study confirm that the RMC material type had a significant influence on bond strength. However, this does not provide consistency with the results of a study by Çelik et al 40 reporting that RMC material type did not significantly cause alterations in bond strength values. They emphasized that only MSC strategy can become influential on bond strength.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study confirm that the RMC material type had a significant influence on bond strength. However, this does not provide consistency with the results of a study by Çelik et al 40 reporting that RMC material type did not significantly cause alterations in bond strength values. They emphasized that only MSC strategy can become influential on bond strength.…”
Section: Discussioncontrasting
confidence: 99%
“…Various surface conditioning strategies are recommended to create micro-porosities (transformed zone) on the bonding surface of the ceramics for better infiltration of the luting cement. 9 17 Supportively, Şişmanoğlu et al 39 and Çelik et al 40 reported favorable outcomes for the RMCs conditioned with different strategies. This is in accordance with the results of the current study as all surface-conditioned silane-free specimens demonstrated significantly higher µSBS values.…”
Section: Discussionmentioning
confidence: 90%
“…With the same laser parameters, the μTBS we recorded for LU was 13.42 MPa and for VE was 1.53 MPa after 10,000 thermal cycling. In another study, it was reported that NY laser treated resin‐ceramic materials (Lava Ultimate, Vita Enamic and GC Cerasmart) showed significantly higher μTBS than control groups (Celik, Sahin, & Dede, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…With the same laser parameters, the μTBS we recorded for LU was 13.42 MPa and for VE was 1.53 MPa after 10,000 thermal cycling. In another study, it was reported that NY laser treated resin-ceramic materials (Lava Ultimate, Vita Enamic and GC Cerasmart) showed significantly higher μTBS than control groups (Celik, Sahin, & Dede, 2019). Shiu et al (2007) reported that the EY laser-treated feldspar ceramic showed low (3.67 MPa) bond strength without any thermalcycle and any other aging procedure.…”
Section: Discussionmentioning
confidence: 98%
“…Fredriksson et al investigated the survival of restored teeth with fiber posts in 236 patients, and reported that only 5 teeth failed at the end of 3 years [2]. Nowadays, hybrid ceramics have been introduced and provide better physical, mechanical, and enhanced flexural properties of ceramics and composites [3]. However, the major disadvantage of these post systems is the uncertainty about the adhesion to root canal dentin.…”
Section: O R I G I N a L Pa P E R © 2021 Polish Dental Associationmentioning
confidence: 99%